INTERPRETING THE CONDITIONS OF BULLYING IN PHOTOBOOK ENTITLED “BULLY” - Mulyono, Tanto Trisno; Astono, Rizky Andika Dwi (PT Altin Riset Publishing, 2024)
This study aims to interpret the conditions of bullying as depicted in the photobook